Medial Meniscal Allograft Transplantation: The Bone Plug Technique - Anna Bartsch MD; Forrest L. Anderson MD; Markus Neubauer MD; Monica S. Vel BS; Seth L. Sherman MD (SAGE Publishing, 2023)
Background: The medial and lateral menisci act as shock absorbers for the knee joint by converting and redistributing axial load into circumferential hoop stresses. Disruptions of these hoop stresses occur in the setting of meniscal deficiency and lead to long-term degenerative changes. Therefore, maintaining the distinctive composition and organization of the menisci is essential. In selective cases of meniscal deficiency, meniscus allograft transplantation can be a valuable treatment option. Indications: Meniscus transplantation should be considered in patients with symptomatic meniscal deficiency, without the presence of advanced degenerative pathologies, who have failed all conservative treatments. Technique description: We can divide the surgery into 4 steps: (1) graft preparation, (2) arthroscopic joint preparation, (3) allograft attachment preparation, and (4) graft fixation. Results: Meniscus allograft transplantation yields good to excellent results in up to 85% of cases. Improvement of pain and knee function occurs in approximately 70% of the patients at 10 years. The associated complications are mainly joint stiffness, early osteoarthritis, and incomplete healing accompanied by graft failure. Graft failure is the most feared complication, yet shows good results over the midterm. Conclusion: The bone plug technique we have shown here is a hybrid approach combining soft tissue and bone fixation techniques. It provides synergistic advantages with good osseous integration and is minimally invasive through arthroscopy without true arthrotomy. In our experience, this approach elegantly eases the complexity of this demanding surgery while yielding excellent results for patients. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.